(untitled) (Eurasian Journal of Philology Science and Education, 2022)
The article discusses the problem of studying the relationship between language, human and environmental principles, describes the theoretical basis of the direction. Particular interest in environmental topical problems and the implementation of these studies in other branches of science, the fact that humanity considers these issues as a necessary condition for future life on Earth. Therefore, the themes of the language and its environment, the preservation of linguistic diversity do not lose their relevance. In this work, the authors analyze the variety of terms in this area, provide fundamental research on each of them. The influence of the analysis of the language and its environment, the connection between the language and the native speaker as a complex of systemic actions on the vitality of the language is investigated. The language is immersed in the environment and the question of the influence of the environment on the language has long been of interest to scientists. Eco-linguistic doctrines developed as a continuation of E. Sapir’s thought that all life experience and the peculiarity of an ethnos are stored in its language. But it should be borne in mind that ecolinguistics as a direction of science appeared relatively recently and there are various approaches to the study of language and its environment. Therefore, the article examines its path of formation as a branch of linguistics and methodological base, analyzes the differences between the terms ecolinguistics, ecology of language, linguoecology. Key words: language, ecosystem, language ecology, linguoecology, ecolinguistics